2019
DOI: 10.1074/mcp.ra119.001710
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Influence of ERAP2 on the HLA-B*40:02 Peptidome: Implications for HLA-B*27-Negative Ankylosing Spondylitis

Abstract: ERAP2 and HLA-B*40:02 are associated with ankylosing spondylitis independently of HLA-B*27. ERAP2 process MHC-I ligands, preferentially trimming N-terminal basic residues. The B*40:02 peptidomes from wild-type and ERAP2-KO cells were compared, which demonstrated a substantial role of ERAP2 on the generation/destruction balance of HLA-B*40:02 ligands. The major effect was on N-terminal residues, although other peptide positions were also affected. We propose that the non-epistatic association of ERAP2 with spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Positive HLA-B*40:02 binding has been established for the human PAM peptide ("KEPGSGVPVVL") and the ANXA7 peptide ("VESGLKTIL") [15][16][17] , that contain the distinctive mimicking SARS-CoV-2 peptides ( Table 1). The closely related HLA-B*40:01 allele also binds this mimicked ANXA7 peptide 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Positive HLA-B*40:02 binding has been established for the human PAM peptide ("KEPGSGVPVVL") and the ANXA7 peptide ("VESGLKTIL") [15][16][17] , that contain the distinctive mimicking SARS-CoV-2 peptides ( Table 1). The closely related HLA-B*40:01 allele also binds this mimicked ANXA7 peptide 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, ESGLKTIL was also found within a 9-meric epitope of SARS-CoV-2, which is known as an HLA-B*40:01 binder. Although HLA-B*40:01 and HLA-B*40:02 are protective for autoimmune hepatitis ( 87 ), these alleles are associated with ankylosing spondylitis (AS) ( 88 , 89 ). Ankylosing spondylitis is associated with SARS-CoV-2 ( 76 ).Besides, positive experimental assays revealed that ESGLKTIL shares sequence identity (more than 90%) with 11-meric and 16-meric peptides from phosphoglycolate phosphatase.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as HLA class I molecules can accommodate longer peptides in their peptide binding cleft [ 112 , 113 , 114 ], ERAP1 polymorphisms that alter protein levels and activity result in the presentation of a different set of ligands in an HLA-B*27 background and, consequently, altered antigenicity. Consistent with the notion that altered peptide characteristics underlie disease pathogenesis, a loss-of-function ERAP2 variant that is associated with AS does not affect MHC class I surface levels, endoplasmic reticulum stress, or inflammatory cytokines production [ 98 , 115 ], but alters the peptidome available for MHC class I presentation [ 116 , 117 ].…”
Section: Models Of Spa Pathogenesis: Hypothesesmentioning
confidence: 96%